ANALISIS PESAN PASTORAL DALAM RITUAL MA’PALUANG DODO PADA ACARA PERKAWINAN WARGA JEMAAT DI MAKKODO - Imanuel Taulangi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study aims to analyze the pastoral message contained in the Ma'paluang dodo ritual at the wedding ceremony of members of the Makkodo Congregation, Simbuang Classis. This study uses a descriptive qualitative approach with a field study method. Data were obtained through unstructured interviews, non-participant observation, and documentation of traditional leaders, church councils, and the local community. The results of the study indicate that the Ma'paluang dodo ritual contains a strong pastoral message, namely (1) affirmation of unity and commitment to marriage through the symbol of the sarong as a symbol of inseparable unity, (2) the formation of independence of couples in resolving household conflicts without involving outsiders, and (3) the integration of cultural values ​​and Christian values ​​such as love, loyalty, and responsibility. This ritual not only functions as a traditional tradition, but also as a medium for contextual pastoral development that shapes the character and readiness of couples in living family life. Thus, this study confirms that local cultural practices have an important contribution in the development of a culture-based pastoral approach.